Forty-five patients with hydatid liver cysts: Preoperative eosinophil and postoperative liver enzyme elevations after cystectomy and resection (Annals of Medical Research, 2023)
Aim:  Although the individualized and multidisciplinary treatment approach is important in the management of liver hydatid cyst, treatment modalities include medical, interventional or minimally invasive, and surgical. Our aim of the study was to investigate the efficacy of eosinophil number and percentage as an inexpensive and practical method that may be useful in the prediction of preoperative recurrence in patients who have undergone surgery for hydatid cysts.Materials and Methods: Patients who underwent surgery for hydatid cyst of the liver at Ege University Hospital in the last 8 years were retrospectively reviewed. Age, sex, history of animal contact, cyst size, ELISA tests, preoperative neutrophils, preoperative eosinophils, preoperative albendazole use, postoperative albendazole use, postoperative AST, postoperative ALT, postoperative INR, complications, and recurrences were analyzed.Results: A total of 45 patients with complete data sets were included. The mean preoperative neutrophil and eosinophil percentages were 60.20% (30%-96%) and 4.57% (1%-41%), respectively. Postoperative complications were seen in 2 patients (4.4%); these complications were collections in the operating lung and cystobiliary fistula. The mean postoperative AST, ALT, INR were 139.13 (12-636), 155.31 (7-569), 1.06 (0.9-2.6), respectively. The mean hospital stay was 13.4 days (2-90). The mean duration of albendazole use in the postoperative period was 3.66 months (1-24 months). Recurrence was observed in 9 cases (20%) during the follow-up period.Conclusion: Although hydatid cysts and eosinophilia are reported in literature, association of eosinophilia with recurrence, size and prognosis is not reported. Our study showed that testing preoperative eosinophils and eosinophil/neutrophil ratio are inexpensive, easily accessible and effective in predicting recurrence. We believe that the validity of the tests will increase as eosinophil percentage and eosinophil/neutrophil percentage (ENPR), for which cut-off values have been established, become more widely used and tested in prospective controlled studies with larger groups.
Keywords: Liver; Hydatid cyst; Eosinophil; Recurrence